Diagnóstico molecular da taxa de infecção natural de flebotomíneos (Psychodidae, Lutzomyia) por Leishmania sp na Amazônia maranhense Molecular diagnosis of the natural infection rate due to Leishmania sp in sandflies (Psychodidae, Lutzomyia) in the Amazon region of Maranhão, Brazil - Yrla Nívea Oliveira-Pereira; José Manuel Macário Rebêlo; Jorge Luiz Pinto Moraes; Silma Regina Ferreira Pereira (Revista da Sociedade Brasileira de Medicina Tropical, 2006)
A taxa de infecção natural de três diferentes espécies de flebotomíneos por Leishmania foi estudada usando a técnica de reação em cadeia da polimerase. Primers específicos para Leishmania foram designados para examinar se os pools de flebotomíneos estavam infectadas. Um total de 1.100 fêmeas separadas em pools de 10 indivíduos foram examinados, consistindo de 50 Lutzomyia whitmani, 43 Lutzomyia triacantha e 17 Lutzomyia choti. De todos os pools analisados, 4 de Lutzomyia whitmani estavam positivos, mas nenhum pool das duas espécies restantes estava infectado. Deste modo, uma taxa de infecção de 0,4% foi verificada neste estudo. Esta taxa de infecção associada a estudos anteriores sugere que Lutzomyia whitmani transmite Leishmania aos mamíferos em Buriticupu, Maranhão. The natural infection rate due to Leishmania was studied in three different sandfly species using the polymerase chain reaction technique. Leishmania specific primers were designed to examine whether sandfly pools were infected. In total 1,100 female sandflies separated into pools of 10 individuals, consisting of 50 pools of Lutzomyia whitmani, 43 of Lutzomyia triacantha and 17 of Lutzomyia choti, were analyzed. Among all the pools examined, four pools of Lutzomyia whitmani were positive, but none of the pools of the other two species were infected. Thus, a total infection rate of 0.4% was established in this study. A similar infection rate was found in previous studies, suggesting that Lutzomyia whitmani transmits Leishmania to mammals in Buriticupu, Maranhão.